2020
DOI: 10.1007/s00134-020-06196-y
|View full text |Cite
|
Sign up to set email alerts
|

Conservative oxygen therapy for mechanically ventilated adults with suspected hypoxic ischaemic encephalopathy

Abstract: Purpose Liberal use of oxygen may contribute to secondary brain injury in patients with hypoxic-ischaemic encephalopathy (HIE). However, there are limited data on the effect of different oxygen regimens on survival and neurological disability in HIE patients. Methods We undertook a post-hoc analysis of the 166 patients with suspected HIE enrolled in a trial comparing conservative oxygen therapy with usual oxygen therapy in 1000 mechanically ventilated ICU patients. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 18 publications
1
38
0
1
Order By: Relevance
“…74À79 A sub-group analysis of a large RCT targeting an arterial blood oxygen saturation of 90À97% compared with 90 À100% showed that in patients at risk of hypoxic-ischaemic brain injury 180-day mortality was lower in the lower oxygen target group 74 ; however, this difference was no longer statistically significant when adjusted for baseline differences. 80 A pilot RCT targeting a PaO 2 of 10À15 kPa compared with 20À25 kPa showed no difference in the values of biomarkers of neurological injury. 75 Overall, the evidence is mixed but suggests targeting normal oxygenation rather than hyperoxaemia.…”
Section: Control Of Oxygenationmentioning
confidence: 97%
“…74À79 A sub-group analysis of a large RCT targeting an arterial blood oxygen saturation of 90À97% compared with 90 À100% showed that in patients at risk of hypoxic-ischaemic brain injury 180-day mortality was lower in the lower oxygen target group 74 ; however, this difference was no longer statistically significant when adjusted for baseline differences. 80 A pilot RCT targeting a PaO 2 of 10À15 kPa compared with 20À25 kPa showed no difference in the values of biomarkers of neurological injury. 75 Overall, the evidence is mixed but suggests targeting normal oxygenation rather than hyperoxaemia.…”
Section: Control Of Oxygenationmentioning
confidence: 97%
“…No difference was observed in the primary outcome measure, the blood levels of neuron specific enolase (NSE), a biomarker of neuronal injury, at 48 h from ROSC. A recent post-hoc analysis [ 31 ] of 166 patients enrolled in the multicentre ICU-ROX trial, which randomised 1000 patients to conservative (SpO 2 90–97%) vs. liberal (SpO 2 90–100%) oxygen therapy, showed that conservative oxygen therapy was not associated with a significant decrease of the odds of survival with poor neurological outcome at 6 months [adjusted odds ratio 0.54 (0.23–1.26)]. The EXACT trial (NCT 03138005) is randomising 1416 resuscitated comatose survivors of OHCA to restrictive (90–94%) vs. liberal (98–100%) oxygen therapy.…”
Section: Treatment Of Pcabimentioning
confidence: 99%
“…In contrast, a post hoc sub-study of the Target Temperature Management (TTM) trial, including 939 patients after out-of-hospital-cardiac arrest, did not find any significant relation between hyperoxaemia (defined as PaO 2 > 300 mmHg) within 37 h of ROSC and poor neurological outcome after 6 months [ 68 ]. Finally, an additional post hoc analysis of the above-mentioned ICU-ROX study including 161 patients with " suspected hypoxic–ischaemic encephalopathy " after cardiac arrest, a subgroup pre-specified and defined prior to randomization, did not show a statistically significant reduction in death or unfavourable neurological outcomes at day 180 [ 69 ]. This finding was in contrast to the analysis of the complete GOSE, which had suggested benefit of the "conservative oxygen" treatment and yielded significantly lower mortality at day 180 in the unadjusted analysis [ 18 ].…”
Section: Cardiopulmonary Resuscitation (Cpr) and Post-cardiac Managementmentioning
confidence: 99%